Meningkatkan Kompetensi Pedagogik Guru Non Akademik dalam Penyusunan Rencana Pelaksanaan Pembelajaran Harian (RPPH) Melalui Supervisi Akademik Kepala Sekolah di TK Negeri 1 Jereweh Tahun Pembelajaran 2018/2019 - Hosniwati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This research is motivated by the lack of cognitive abilities in recognizing the shapes and colors of objects in Group B TK Negeri 1 Jereweh, and varied games are rarely applied to the cognitive development of children. The formulation of the problem in this study is: